FORMULASI DAN EVALUASI SIFAT FISIK SEDIAAN GEL EKSTRAK ETANOL DAUN PETAI CINA (Leucanea leucocephala (Lam.) de Wit) DENGAN VARIASI KONSENTRASI BASIS KARBOPOL 940 - Suri, Natasha Triska; Nawangsari, Desy; Febrina, Dina (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Chinese petai leaves (Leucaena leucocephala (Lam.) De Wit.) contain compounds in the flavonoid, saponin, and tannin groups that have antioxidant activity. Chinese petai leaves need to be developed in the form of a gel preparation with a karbopol 940 base. Karbopol 940 is a gelling agent that is very commonly used in cosmetic production due to its high compatibility and stability, non-toxicity when applied to the skin, and ease of spreading on the skin. This study aims to determine the formulation of ethanol extract gel from petai cina leaves with physical properties and physical stability, to assess the irritation effects on the skin of albino rabbits, and to evaluate the respondents' preference for the gel preparation. This research is an experimental study. The extraction method used was maceration with 70% ethanol as the solvent. The formulation of the ethanol extract gel from the Chinese petai leaves used a carbopol 940 base with concentration differences of F1 0,5%, F2 1%, and F3 2%. The research results showed that the organoleptic physical properties had a distinctive smell, were brown in color, and had a gel form. The homogeneity test indicated that the gel preparation was homogeneous. The pH test results met the standards. Based on statistical testing, it was found that pH, viscosity, and spreadability obtained p-value <0,05, indicating a significant difference due to the varying concentrations of carbopol used in each formula. The adhesion test results did not show a significant effect. In the irritation test, it showed very mild irritation and the preference level indicated the highest percentage of 34,60%.